Laws and Politics of the International Relations of Japan and the United States - Angelo, A H (Victoria University of Wellington Law Review, 1997)
This article is a book review of Makitaro Hotta Laws and Politics of the International Relations of Japan and the United States (published jointly by the School of International Service, American University, Washington, and the College of International Relations, Ritsumeikan University, Kyoto, 1996) 195 pages. The book is a compendium of documents and materials relating to Japan and United States relations from the Cairo Declaration of 1 December 1943 to the Japan/US Joint Declaration on Security Alliance for the 21st Century of 17 April 1996. Angelo praises the book’s versatility, as it can be used for comparative law classes and for international relations programmes, for constitutional law teaching, and for aspects of public international law.